PENGARUH SELEKSI DAN PENEMPATAN JABATAN SUMBER DAYA MANUSIA TERHADAP KINERJA KARYAWAN PADA PERUSAHAAN DAERAH AIR MINUM (PDAM) KABUPATEN ENREKANG - Sulfiana, Sulfiana; Deasy Soraya A.Aminartha; Nur Asisah (Program Studi Manajemen Fakultas Ekonomi dan Bisnis, 2022)
This study aims to determine the effect of selection and placement of human resources on employee performance at the Perusahaan Daerah Air Minum (PDAM) of Enrekang Regency. The technique used to obtain data by means of observation, interviews, and questionnaires. The sample in this study is 60 respondents. The data analysis technique in this study uses multiple linear regression analysis, to ensure that the independent variable has an influence on the dependent variable, then performs hypothesis testing in finding out the significance of the independent variable on the dependent variable as well as making conclusions and calculating the determinant coefficient in finding out the magnitude of the thing affect the independent variable on the dependent variable. The data analysis technique used with the help of SPSS Version 23. The results studied in order to find a discussion for the thing being studied are the results of partial hypothesis testing showing that the selection variable (X1) and job placement (X2) have a positive and significant impact on employee performance at the Perusahaan Daerah Air Minum (PDAM) of Enrekang Regency. This can be seen from the acceptance of Ha and the rejection of Ho. So the hypothesis which reads that there are things that affect employee performance on selection and placement at the Perusahaan Daerah Air Minum (PDAM) of Enrekang Regency